1988
DOI: 10.1161/01.cir.77.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative rotational thallium-201 tomography for identifying and localizing coronary artery disease.

Abstract: The purpose of this study was to develop and validate a method for quantifying the uptake, redistribution, and washout of thallium-201 (201T1) obtained with rotational tomography. This method generates maximum count circumferential profiles of the short-axis slices of the left ventricle, translates them into polar coordinate profiles, and displays them as a bullseye plot, which consists of a series of concentric circles with the apex at the center and the base at the periphery. Normal limits were established f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
1
5

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(85 citation statements)
references
References 30 publications
2
77
1
5
Order By: Relevance
“…A este respecto es interesante destacar el trabajo de De Pasquale EE et al 10 , quienes vieron que la sensibilidad para la detección de compromiso de un vaso coronario, sólo con el bullseye fue 78% para la ADA, 89% para la arteria coronaria derecha y 65% para la circunfleja.…”
Section: Discussionunclassified
“…A este respecto es interesante destacar el trabajo de De Pasquale EE et al 10 , quienes vieron que la sensibilidad para la detección de compromiso de un vaso coronario, sólo con el bullseye fue 78% para la ADA, 89% para la arteria coronaria derecha y 65% para la circunfleja.…”
Section: Discussionunclassified
“…The results showed that in patients with angina pectoris, proximal LAD stenosis can be predicted with reliable accuracy by recognizing defect patterns. Polar map displays were useful because they allowed more objective and simultaneous visual evaluation of the whole myocardium, 6,10 but evaluation of tomographic images was also necessary to avoid false-positive interpretations. 11 By using proximal LAD patterns on a polar map, proximal LAD stenosis could be detected with a sensitivity of 72% and a high specificity of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a widely available noninvasive test that can identify proximal LAD stenosis could have substantial clinical utility. Thallium-201 single-photon emission computed tomography (SPECT) is widely utilized to evaluate myocardial ischemia, 6,7 and the location and pattern of perfusion defects often implicates which coronary artery is likely to be responsible. 8 However, the ability of thallium-201 SPECT findings for identifying proximal LAD stenosis has not been thoroughly evaluated.…”
mentioning
confidence: 99%
“…Filling defects were diagnosed as ischemia when the two contiguous slices showed reversibility or when bull's-eye mapping showed a decrease in the intensity of perfusion defects of more than 10% in the redistribution phase. 16,17 …”
Section: Stress Myocardial Perfusion Imagingmentioning
confidence: 99%